Предмет: Алгебра,
автор: sheverdavladik17
Упростите выражение (4а + 3b)² - (2a - b)(5a - 9b)
Ответы
Автор ответа:
1
Ответ:
Давайте раскроем скобки:
(4a + 3b)² = (4a)² + 2(4a)(3b) + (3b)² = 16a² + 24ab + 9b²
(2a - b)(5a - 9b) = 10a² - 18ab - 5ab + 9b² = 10a² - 23ab + 9b²
Теперь подставим значения в исходное выражение:
(4a + 3b)² - (2a - b)(5a - 9b) = (16a² + 24ab + 9b²) - (10a² - 23ab + 9b²) = 6a² + 47ab
Ответ: 6a² + 47ab.
Объяснение:
Похожие вопросы
Предмет: География,
автор: Аноним
Предмет: Геометрия,
автор: fctdgsygfdhngfxzgsac
Предмет: Литература,
автор: lanliiiii
Предмет: Алгебра,
автор: Аноним